Pelvic Radiation Disease Management by Hyperbaric Oxygen Therapy: Prospective Study of 44 Patients - Mehdi Ouaïssi; Stephanie Tran; Diane Mege; Vivien Latrasse; Alain Barthelemy; Nicolas Pirro; Philippe Grandval; James Lassey; Igor Sielezneff; Bernard Sastre; Mathieu Coulange (Gastroenterology Research and Practice)
Pelvic radiation disease (PRD) occurs in 2–11% of patients undergoing pelvic radiation for urologic and gynecologic malignancies. Hyperbaric oxygen therapy (HBOT) has previously been described as a noninvasive therapeutic option for the treatment of PRD. the purpose of study was to analyze prospectively the results of HBOT in 44 consecutive patients with PRD who were resistant to conventional oral or topical treatments. Material and Methods. The median age of the cohort was 65.7 years (39–85). Twenty-seven percent of patients required blood transfusion (n=12). The median of delay between radiotherapy and HBOT was 26 months (3–175). We evaluated the results of HBOT, using SOMA-LENT Scale. Results. SOMA-LENT score was decreased in 59% of patient. The median of SOMA-LENT score before HBOT was significantly higher, being equal to 14 (0–36), than after HBOT with the SOMA-LENT score of 12 (0–38) (P=0.003). Tenesmus (P=0.02), bleeding (P=0.0001), and ulceration (P=0.001) significantly decreased after HBOT. Regarding patients with colostomy, 33% (n=4) benefited from colostomies closure. HBOT was generally well tolerated. Only one patient stopped precociously due to transient myopia. Conclusion. This study is in favor of the interest of HBOT in pelvic radiation disease treatment (PRD).